Chasing as a model of psychogenic stress: characterization of physiological and behavioral responses. (4th July 2018) - Lee, Ji-Hye; Kimm, Sunwhi; Han, Jung-Soo; Choi, June-Seek
Abstract: Being chased by a predator or a dominant conspecific can induce significant stress. However, only a limited number of laboratory studies have employed chasing by itself as a stressor. In this study, we developed a novel stress paradigm in which rats were chased by a fast-moving object in an inescapable maze. In Experiment 1, defensive behaviors and stress hormone changes induced by chasing stress were measured. During the chasing stress, the chasing-stress group ( n  = 9) froze and emitted 22-kHz ultrasonic vocalizations (USVs), but the no-chasing control group ( n  = 10) did not. Plasma corticosterone levels significantly increased following the chasing and were comparable to those of the restraint-stress group ( n  = 6). In Experiment 2, the long-lasting memory of the chasing event was tested after three weeks. The chasing-stress group ( n  = 15) showed higher levels of freezing and USV than the no-chasing group ( n  = 14) when they were presented with the tone associated with the object's chasing action. Subsequently, the rats were subjected to Pavlovian threat conditioning with a tone as a conditioned stimulus and footshock as an unconditioned stimulus. The chasing-stress group showed higher levels of freezing and USV during the conditioning session than the no-chasing group, indicating sensitized defensive reactions in a different threat situation. Taken together, the current results suggest that chasing stress can induce long-lasting memory and sensitization of defensive responses to a new aversive event as well as immediate, significant stress responses.